Cytotoxicity of leukemic cells by nypa fruticans through regulation of adiponectin expression - Zainudin, Mohammad Fauzan; Fadzir, Ummu Afifah; Rosdi, Athirah; Johan, Muhammad Farid; Hashim, Ridzwan; Abdul Wahab, Ridhwan; Mamat, Suhana (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2017)
Introduction: Acute lymphoblastic leukemia (ALL) is the most common leukemia subtypes among paediatrics in Malaysia. Although treatment options are available but some patients remain incurable, some undergo relapse and many experiences adverse effects by the conventional therapies. Thus, we aim to investigate possible treatment alternative by studying the antileukemogenesis properties of concentrated Nypa fruticans sap called nisaan by focusing on adiponectin expression.